Pengaruh Penerapan E-filling Dan Pemahaman Perpajakan Terhadap Kepatuhan Wajib Pajak Orang Pribadi Pada Kantor Pelayanan Pajak Batam Selatan - Siregar, Yentina (University of Riau Kepulauan, 2019)
The implementation of e-filling is a step that the DGT expects to be able to improve individual taxpayer compliance. Many factors that can affect taxpayers are still not compliant in paying or reporting annual tax returns, which is perhaps one of them is understanding taxation. This research is quantitative with the sampling technique used is purposive sampling. The criteria set for taking samples in this study are individual taxpayers who have used e-filling and registered with the South Batam KPP and collected data using questionnaires distributed online and directly to respondents the number of questionnaires distributed was 110 respondents and those who returned and can be processed as many as 105 respondents. The results obtained from this study are (1) the application of e-filling has a significant effect on individual taxpayer compliance with a sig value of 0.038 (2) understanding of taxation has a significant effect on individual taxpayer compliance with a sig value of 0.002 (3) simultaneously the application of e-filling and understanding of taxation have a significant effect on individual taxpayer compliance with a value of sig 0,000.Â Keywords: Compliance of Individual Taxpayers, Implementation of E-filling, Understanding of Taxation.Â